Perintah Kelima: Suatu Prinsip yang Menandai Kehidupan Orang Percaya - Retjelina, Dorkas (Sekolah Tinggi Teologi Berea, Salatiga, 2021)
The purpose of this article is for every believer to understand and carry out the commandments to obey and respect their parents. There are many cases where children disobey their parents and lead to conflicts. They sued their parents to court and someone had the heart to kill their parents. Why is that? Don't they know the timeless principle of honoring parents? Several articles have written about obedience and respect for parents, but the emphasis on obedience and respect for people who are worthy of being called parents and the broader consequences of obedient and respectful behavior is not emphasized. Through qualitative research methods of biblical studies, this paper will explain that the correct understanding of the fifth commandment in Deuteronomy 5 verse 16 is very important teaching. That is why this research focuses on Deuteronomy chapter 5 about the giving of the Ten Words and specifically on verse 16 which talks about honoring parents. To achieve the proof, the first part will describe cases of disobedience of children to parents that lead to conflicts. The second part exegesizes Deuteronomy chapter 5 verse 16. The third part shows the importance of respecting parents.